Connecting theory and practice: women scientist role models in television programming. - Steinke, Jocelyn (Journal of Broadcasting & Electronic Media)
Bem's gender schema theory (Bem 1981, 1983, 1993) provides a useful framework for examining the influence of women scientist role models on girls' perceptions of science and scientists. The purpose of this paper is (1) to describe how Bem's gender schema theory serves as a framework for guiding future research, (2) to examine the fundamental premises of Bem's gender schema theory as they relate to the processing of information about science and gender roles, and (3) to identify key conditions and criteria from gender schema theory to guide the design of television programs that use role models to reduce gender-stereotyping of science. Reprinted by permission of the publisher.